APPLICATION OF CRITICAL THINKING TO IMPROVE STUDENT LEARNING OUTCOMES KNOWLEDGE OF LATHE MACHINERY IN TURNING - Alverro Pratama Widodo; Heri Yudiono (Jurnal Pendidikan Teknik Mesin, 2023)
Education is closely related to learning both in class and outside the classroom, especially practicum. Lathe machining practicum as a practical lesson cannot be separated from students' knowledge, skills,  and critical thinking in completing the practicum. This study aims to determine the effect of critical thinking on lathe machining practicum and test the results of increasing student learning outcomes of lathe machining practicum on critical thinking instrument models. Using the true-experimental design method with a pretest-posttest control group design. The research subjects were students of the Mechanical Engineering Education Study Program, The Faculty of Engineering, Semarang State University for the 2019/2020 academic year consisted of 84 students which were  divided into an experimental group and a control group with 42 students in each group, then used a sampling technique in the form of cluster sampling. He gave test questions and questionnaires to each group at the beginning and end (pretest and posttest) and discussed and analyzed the workpiece design from the learning videos for the experimental group while the control group was not given any treatment. The results showed that the critical thinking level of lathe machining practicum students in the experimental group was higher than that of the control group and there was an increase in learning outcomes in the application of critical thinking. Using the discussion method in the learning process can increase the level of critical thinking of students so that students can solve problems better. The discussion method in learning can be applied to other learning models to improve student’s critical thinking and student learning outcomes.